2004
DOI: 10.1164/rccm.200301-104oc
|View full text |Cite
|
Sign up to set email alerts
|

Natural Porcine Surfactant Augments Airway Inflammation after Allergen Challenge in Patients with Asthma

Abstract: There is increasing evidence for a role of pulmonary surfactant in asthma and allergic inflammation. In murine asthma models, recent studies have demonstrated that surfactant components downregulate the allergic inflammation. Therefore, we tested the hypothesis that in individuals with mild asthma, a natural porcine surfactant preparation (Curosurf) given before segmental allergen challenge can reduce the allergic airway inflammation. Ten patients with asthma and five healthy control subjects were treated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 37 publications
1
54
0
Order By: Relevance
“…Babu et al (1) showed that pulmonary surfactant dysfunction may also contribute to the very early asthmatic response to allergen and that exogenous surfactant administration could serve as a useful adjunct in controlling the early allergen-induced symptoms in patients with allergic asthma. Other studies raise concerns over the use of surfactant replacement materials sourced from animals, suggesting species differences in biochemistry and function of surfactant and highlighting a lack of understanding of the surfactant system (10). Inhibition or overload of the surfactant system by urban PM inhalation and surfactant sequestration may therefore be related to the observed health effects of PM exposure, such as increased infections in PM exposed rats (41) and PM exposed humans (9,27).…”
Section: Discussionmentioning
confidence: 99%
“…Babu et al (1) showed that pulmonary surfactant dysfunction may also contribute to the very early asthmatic response to allergen and that exogenous surfactant administration could serve as a useful adjunct in controlling the early allergen-induced symptoms in patients with allergic asthma. Other studies raise concerns over the use of surfactant replacement materials sourced from animals, suggesting species differences in biochemistry and function of surfactant and highlighting a lack of understanding of the surfactant system (10). Inhibition or overload of the surfactant system by urban PM inhalation and surfactant sequestration may therefore be related to the observed health effects of PM exposure, such as increased infections in PM exposed rats (41) and PM exposed humans (9,27).…”
Section: Discussionmentioning
confidence: 99%
“…The instilled amount of antigen was 10–1,000 SQ-U diluted in 10 ml of saline solution. Bronchial hyperresponsiveness and the provocative concentration of methacholine that reduced forced expiratory volume in 1 s by 20% (PC 20 ) were determined as described [25]. Patients only used salbutamol when required for relief of symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…To determine the allergen dose for the segmental instillation, a skinprick test with a dilution series of the allergen extract in saline was done as previously described (26). The allergen concentration that elicited at least a 3-mm-diameter skin weal response was selected for instillation (100-100.000 SQE diluted in 10 ml saline).…”
Section: Dosage and Preparation Of Challenge Substancesmentioning
confidence: 99%